DEVELOPMENT OF A TECHNIQUE TO DETERMINE ADEQUATE SAMPLE SIZE USING SUBSAMPLING AND RETURN INTERVAL ESTIMATION - Porth L.S.; Boes D.C.; Davis R.A.; Troendle C.A.; King R.M. (My University, 2001)
To better manage aquatic and riparian ecosystems, knowledge of streamflow return intervals is essential. This leads hydrologists and planners to often question how many years of record are necessary to adequately estimate streamflow characteristics. We propose a nonparametric technique that uses subsampling and return interval estimation to help determine adequate sample size, in order to help answer this question. This technique was applied to 51years of streamflow record from an untreated catchment known as East St. Louis Creek in the Fraser Experimental Forest. Subsamples of consecutive streamflow record ranging in size from 5 to 25years were used to empirically estimate the 1.5-, 5-, and 15-year return intervals. These subsample estimates were compared to the 'true' return intervals, which were calculated using the entire period of record. Results showed that an ability to estimate these return intervals within 50% of the true return interval levels required only 5-10years of data. Increasing the sample size to 15years provided estimates with up to a 25% error rate, and 25 or more years of data were required to provide estimates with less than a 20% error. These are simply the results of a case study, and could be applied to similar catchments. However, the methodology can be applied to any stream.
Keywords: STREAMFLOW; RECURRENCE INTERVAL; FLOOD FREQUENCY; SAMPLING; PREDICTION; SAMPLE SIZE